(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
This study determines the effect of Sulphuric acid on the compressive strength of concrete with Quarry Dust as partial replacement of fine aggregate at 0 %, 15 %, 25 % and 35 %. A total of seventy-two (72) 100 mm cubes were cast and cured in water up to 28 days. The Compressive strength test was done on the first 36 cubes at 7, 14 and 28 days, while the remaining 36 cubes were exposed to 5 % prepared solution of sulphuric acid after 28 days in water and crushed at 7, 14 and 28 days. The results obtained indicated that the slump decreases as the percentage addition of Quarry Dust increases. However, the result of the compressive strength of Quarry Dust-concrete showed that the compressive strength increased with the curing age and also increased with the addition of Quarry Dust. On the other hand, the resistance of the concrete to acid increases as the percentage addition of Quarry Dust increases. The weight of concrete decreased with an increase in exposure duration and also decreased with an increase in Quarry Dust content. But the water absorption of Quarry Dust-Concrete decreased with an increase in Quarry Dust addition. It can be concluded that Quarry Dust can replace river sand in concrete to improve its resistance to sulphuric acid attack